Gillett, Nicholas, "Abolishing War: One Man's Attempt" - Phillips, Brian (Quaker studies, 2006)
GILLETT, Nicholas, Abolishing War: One Man's Attempt (York: William Sessions Limited, 2005), pp. xii + 394. ISBN 1-85072-321-4. Paper, £15.00.